Biological activities, Peptidomics and in silico analysis of low-fat Cheddar cheese after in vitro digestion: Impact of blending camel and bovine Milk - Ali, Abdelmoneim H.; Ozturk, Hale Inci; Eylem, Cemil Can; Nemutlu, Emirhan; Tarique, Mohammad; Subhash, Athira; Liu, Shao-Quan; Kamal-Eldin, Afaf; Ayyash, Mutamed (ELSEVIER SCI LTD, 2024)
Cheesemaking with camel milk (CM) presents unique challenges and additional health benefits. This study involved preparing low-fat Cheddar cheese (LFCC) by blending bovine milk (BM) with varying levels of CM. Control cheese was made exclusively with BM. After 180 days of ripening, LFCC samples underwent in vitro digestion to determine antioxidant capacities, alpha-amylase and alpha-glucosidase inhibition, and angiotensinconverting enzyme inhibition. The peptide profile of LFCC treatments was analyzed using liquid chromatography-quadrupole-time of flight-mass spectrometry. Antioxidant and biological activities were influenced by BM-CM blends and digestion. At days 120 and 180, the number of alpha s1-casein-derived peptides increased in all samples except for LFCC made with 15% CM. Generally, 88 peptides exhibited ACE inhibition activity after 120 days of ripening, increasing to 114 by day 180. These findings suggest that ripening time positively affects the health-promoting aspects of functional cheese products.
Keywords: Camel milk cheese; Ripening; Biological activity; Peptidomes; In silico analysis; LC-Q-TOF-MS; CONVERTING-ENZYME ACE; ANTIOXIDANT ACTIVITY; BIOACTIVE PEPTIDES; PROTEOLYSIS; CASEIN; FUNCTIONALITY; INHIBITION; HYDROLYSIS; PROTEINS; BUFFALO; Chemistry; Food Science & Technology; Nutrition & Dietetics